2003
DOI: 10.1093/carcin/bgg011
|View full text |Cite
|
Sign up to set email alerts
|

Changes in global gene and protein expression during early mouse liver carcinogenesis induced by non-genotoxic model carcinogens oxazepam and Wyeth-14,643

Abstract: We hypothesized that the mouse liver tumor response to non-genotoxic carcinogens would involve some common early gene and protein expression changes that could ultimately be used to predict chemical hepatocarcinogenesis. In order to identify a panel of genes to test, we analyzed global differences in gene and protein expression in livers from B6C3F1 mice following dietary treatment with two rodent carcinogens, the benzodiazepine anti-anxiety drug oxazepam (2500 p.p.m.) and the hypolipidemic agent Wyeth (Wy)-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 82 publications
4
43
0
Order By: Relevance
“…Other notable alterations in gene expression were the overexpression of IGFBP-1 and suppression of insulin-like growth factor 1 (IGF-1). Chronic exposure to nongenotoxic chemicals such as oxazepam and Wyeth-14,643 increased the expression of IGFBP-1 in a time-dependent manner (Iida et al 2003), and overexpression of IGFBP-1 was also seen in transplacental arsenic-induced HCC and tumor-surrounding tissues ). Dysregulation of the IGF axis has been implicated in liver tumor formation and progression (Scharf et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Other notable alterations in gene expression were the overexpression of IGFBP-1 and suppression of insulin-like growth factor 1 (IGF-1). Chronic exposure to nongenotoxic chemicals such as oxazepam and Wyeth-14,643 increased the expression of IGFBP-1 in a time-dependent manner (Iida et al 2003), and overexpression of IGFBP-1 was also seen in transplacental arsenic-induced HCC and tumor-surrounding tissues ). Dysregulation of the IGF axis has been implicated in liver tumor formation and progression (Scharf et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…After exposure to N-nitrosomorpholine, the expression of malignancy-associated proteins such as caspase-8, vimentin and Rho GDP dissociation inhibitor were seen after 3 weeks of drug treatment whilst transformed cells were seen only after 18 weeks [55]. Similarly, many protein expression changes seen after 6 months of exposure to oxazepam and Wyeth-14,643 were already seen after exposure for 2 weeks [54]. It was notable that, whilst both oxazepam and Wyeth-14,643 are carcinogenic in rodents, they each caused changes in different groups of proteins, suggesting that they may have different mechanisms of carcinogenesis.…”
Section: Time-related Adverse Drug Reactionsmentioning
confidence: 98%
“…Typically, drugs are tested over an extended time in rodents to investigate these effects and to assist in predicting the likelihood of adverse time-related effects in humans. Time course studies of drugs and carcinogens known to cause liver cancer in rodents (oxazepam, Wyeth-14,643 and Nnitrosomorpholine), have recently been combined with proteomic analyses [54,55]. In these studies, 2-D PAGE revealed dramatic changes in protein expression in the liver prior to the onset of carcinogenesis.…”
Section: Time-related Adverse Drug Reactionsmentioning
confidence: 99%
“…To investigate proteins involved in peroxisome proliferation, Chu et al (2002) compared the protein profiles of acyl-CoA oxidase-deficient and peroxisome proliferator-treated mouse liver with SEL-DI-TOF-MS. With 2D-PAGE-MS, Zeindl-Eberhart et al (2001, 2004 compared the protein profiles of rat HCC tissues induced by genotoxic or non-genotoxic carcinogens and identified aldose reductase-like variants among HCCs induced by carcinogens of different categories. Protein profiles of mouse HCCs induced by two different drugs of the same non-genotoxic category were distinct, demonstrating the great heterogeneity of pathways activated in HCC (Iida et al, 2003). Differentially expressed proteins in animal models can possibly be used as potential biomarkers for HCC diagnosis or targets for HCC chemotherapy as demonstrated in Zeindl-Eberhart's study; variants of aldose reductase-like proteins, which were found differentially expressed in rat HCC, were further validated as potential biomarkers for human HCC by immunohistology (Zeindl-Eberhart et al, 2004).…”
Section: Tumor Tissuesmentioning
confidence: 99%